2013
DOI: 10.3324/haematol.2013.089565
|View full text |Cite
|
Sign up to set email alerts
|

Intentional donor lymphocyte-induced limited acute graft-versus-host disease is essential for long-term survival of relapsed acute myeloid leukemia after allogeneic stem cell transplantation

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nGvL response in relapsed AML, a rapid, large amplitude immune response is likely to be required, since the fast proliferation rate of an acute leukemia can lead to a high tumor burden, which will suppress the immune response. 19,20 A rapid and profound immune response is, however, likely to come at the cost of GvHD.To maximize the effect of combined cytoreductive treatment and DLI administration, we adopted a therapeutic strategy for post-allogeneic SCT relapsed A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…If initially profound T cell depletion is applied to prevent development of GVHD, the GVL reactivity must be reintroduced by postponed DLI. Balance between the beneficial GVL reactivity and GVHD is dependent on the dose of infused T cells and the time interval between transplantation and DLI and is obviously also dependent on the immunogenetic mismatch between donor and recipient (Barge et al., 2003; Eefting et al., 2014a, 2014b). At the time of stem cell transplantation early after conditioning of the patient inflammatory conditions, lymphopenia of the patient, and the high frequencies of patient derived activated APCs, will lead to profound immune responses which are likely to include clinical signs of GVHD.…”
Section: T Cell Separations To Modify Allo‐immune Responses After Tramentioning
confidence: 99%
“…If initially profound T cell depletion is applied to prevent development of GVHD, the GVL reactivity must be reintroduced by postponed DLI. Balance between the beneficial GVL reactivity and GVHD is dependent on the dose of infused T cells and the time interval between transplantation and DLI and is obviously also dependent on the immunogenetic mismatch between donor and recipient (Barge et al., 2003; Eefting et al., 2014a, 2014b). At the time of stem cell transplantation early after conditioning of the patient inflammatory conditions, lymphopenia of the patient, and the high frequencies of patient derived activated APCs, will lead to profound immune responses which are likely to include clinical signs of GVHD.…”
Section: T Cell Separations To Modify Allo‐immune Responses After Tramentioning
confidence: 99%
“…T cell depletion of the graft can prevent GVHD but also impairs development of the associated GVL effect (5,6). Persistent or recurring malignant hematopoietic cells after allo-SCT will then require elimination by subsequent donor lymphocyte infusion (DLI) (7)(8)(9)(10)(11)(12). The observation that T cell depletion followed by postponed DLI reduces the development of GVHD after alloSCT can be explained by the timing of DLI, when prealloSCT chemotherapy-induced tissue damage and infections have largely been resolved, the "cytokine storm" has subsided, and patient-derived antigen-presenting cells (APC) that can induce an immune response are gradually being replaced by donor APCs (3,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Some groups have administered interferon-alpha to promote GVHD in hopes of improving disease response. ( 16 , 17 ) DLI has been given along with chemotherapy and concurrent immunosuppression to reduce GVHD rates. Using this approach, Yan et al reported higher CR rates compared to chemotherapy alone, suggesting that despite the post-DLI immunosuppression, the GVL effect was still clinically evident.…”
Section: Discussionmentioning
confidence: 99%